Pengaruh Dimensi Service Quality Terhadap Kepuasan Pelanggan Rumah Sakit Benyamin Guluh (RSBG) Kolaka - Karmila Karmila; Ismanto Ismanto; Fitri Kumalasari (Jurnal Manajemen Kreatif dan Inovasi, 2023)
The objectives of this research are to determine the following: (1) Tangible influence on Kolaka RSBG customer satisfaction, (2) Reliability influence on Kolaka RSBG customer satisfaction, (3) Responsiveness influence on Kolaka RSBG customer satisfaction, (4) Assurance influence on Kolaka RSBG customer satisfaction, and (5) Empathy influence on Kolaka RSBG customer satisfaction. The sample in this research has 122 respondens, which used the sampling technique known as incidental sampling. Instrumen in this research used validity tests and reliability tests with SPSS 22.0. Research data analysis techniques used the Structural Equation Method Modeling (SEM-PLS) with SmartPLS 4.0. Based on the results of the research, it could be conculed that while Tangible variables had a positive and significant impact on customer satisfaction, as shown by their T-Statistic value of 3.667 and P-Values of 0.000, the Reliability variable’s impact on customer satisfaction has both positive and significant.This is shown by their T-Statistic value of 0,079 and P-Value of 0,469. With a T-Statistic value of 2.695 and P-Value of 0.004, the variable Responsiveness had a positive and significant impact on customer satisfaction, whereas the variable assurance had a negative and negligible impact. The Empathy variable had a positive and substantial impact on Customer Satisfaction , as shown by a T-Statistic value of 1.647 and P-Values of 0.050. Customer are indicated by a T-Statistic value of 0.867 and P-Values of 0,185.